2003
DOI: 10.1128/aem.69.11.6954-6958.2003
|View full text |Cite
|
Sign up to set email alerts
|

Phenylacetic and Phenylpropionic Acids Do Not Affect Xylan Degradation by Ruminococcus albus

Abstract: Since the addition of either ruminal fluid or a combination of phenylacetic and phenylpropionic acids (PAA/PPA) has previously been shown to dramatically improve cellulose degradation and growth of Ruminococcus albus, it was of interest to determine the effects of these additives on xylan-grown cultures. Although cell-bound xylanase activity increased when either PAA/PPA or ruminal fluid was added to the growth medium, total xylanase did not change, and neither of these supplements affected the growth or xylan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…R. albus 8 was kindly provided by M. A. Cotta (USDA-NCAUR, Peoria, IL, USA) and was routinely cultured in EM-cellobiose medium (Reveneau et al, 2003) alone or supplemented with 5 % (v/v) clarified rumen fluid or 25 mM of both phenylacetic acid (PAA) and phenylpropionic acid (PPA) (Sigma). R. albus 20 (=ATCC 27211) and its adhesiondefective mutant R. albus D5 were cultivated in a rumen fluid medium with 0?3 % (w/v) cellobiose (RF cellobiose medium; Mosoni & Gaillard-Martinie, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…R. albus 8 was kindly provided by M. A. Cotta (USDA-NCAUR, Peoria, IL, USA) and was routinely cultured in EM-cellobiose medium (Reveneau et al, 2003) alone or supplemented with 5 % (v/v) clarified rumen fluid or 25 mM of both phenylacetic acid (PAA) and phenylpropionic acid (PPA) (Sigma). R. albus 20 (=ATCC 27211) and its adhesiondefective mutant R. albus D5 were cultivated in a rumen fluid medium with 0?3 % (w/v) cellobiose (RF cellobiose medium; Mosoni & Gaillard-Martinie, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Water-soluble and insoluble forms of residual xylan were precipitated by the addition of 1 M perchloric acid to culture samples [24], centrifuged at 10,000g for 15 min and the xylan content measured using xylose as standard. Three milliliters of the test solution was mixed with equal volume of orcinol reagent and the solutions were boiled for 20 min in a water bath.…”
Section: Determination Of Residual Cellulose and Xylanmentioning
confidence: 99%
“…Cotta (1993) observed a 46% utilization of OSX substrate by R. albus 7 after 24 h growth on a trypticase-yeast extract medium. However, Reveneau et al (2003) noted incomplete degradation of xylan by R. albus and suggested that cessation of xylan degradation and growth of R. albus may be due to xylose accumulation. This may be the case in the present study, since sugar exhaustion cannot be the cause of cessation of growth as there was a lot of sugar left un-utilized (Table 3).…”
Section: Growth and Sugar Utilizationmentioning
confidence: 99%
“…A study by Reveneau et al (2003) on the possible effects of phenyl acids (PAA and PPA) or other components of rumen fluid on xylan degradation and growth of R. albus showed that the addition of phenyl acids (or other components present in rumen fluid) had no influence on xylan (OSX and Birchwood) degradation or the growth of any of the R. albus strains (8, 7 and B199) tested. In their study they recorded 49% xylan degradation after 24 h incubation of R. albus 8 cultures supplemented with phenyl acids.…”
Section: Growth and Sugar Utilizationmentioning
confidence: 99%
See 1 more Smart Citation